Optimalisasi Manajemen Pendidikan dalam Menghadapi Beban Administrasi Dosen: Implikasi terhadap Kualitas Pengajaran di IAIN Curup - Deli Susanti; Warsah, Idi; Warlizasusi, Jumira (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to explore the impact of administrative workload on the teaching quality of lecturers at IAIN Curup, focusing on optimizing educational management to enhance teaching effectiveness. Employing a mixed methods approach, the study integrates qualitative data from in-depth interviews with lecturers and administrators and quantitative data gathered through surveys of 50 lecturers at IAIN Curup. The findings indicate that excessive administrative tasks disrupt lecturers' concentration during the teaching process, negatively affect teaching quality, and reduce time management efficiency. Based on these findings, the study proposes strategies for optimizing educational management, including a more equitable distribution of administrative duties, the use of digital technology to streamline administrative processes, and increased managerial support from the institution. This research provides significant contributions to the development of more efficient educational management practices in the context of Islamic higher education institutions.